Características clínico-epidemiológicas de alopecia androgenética en pacientes del Hospital Regional Docente de Trujillo - Alfaro Paredes, Katherinne Geraldine (2023)
Androgenetic alopecia (AGA) is progressive hair loss characterized by miniaturization of the hair follicle with a characteristic pattern according to sex and multifactorial origin. Objective: To determine the clinical-epidemiological characteristics of AGA in adult patients of the Hospital Regional Docente de Trujillo from March 23 to September 23, 2022. Methods: Prospective descriptive observational study. Information was obtained through data collection forms of patients over 18 years of age with a diagnosis of AGA. Results: Of 40 patients with AGA, 55% were male and 45% female, mainly aged 31-49 years and with family history of AAG (72.5%). In males the typical grade IIIv pattern prevailed in those aged 31-49 years; and in females the diffuse grade I pattern (25%) in <70 years. The most common disease time was 1-5 years, with negative pull test, in women (27.5%) and in 31 - 49 years (27.5%). Conclusions: Most patients were 31-39 years old, male and with family history of AAG; typical grade II and IIIv and diffuse grade I pattern predominated; disease time of 1-5 years and negative pull test.